Factors associated with the presence of parafoveal scotoma in glaucomatous eyes with optic disc hemorrhages. (October 2018) - Dias, Diego; Almeida, Izabela; Sassaki, Adriana; Juncal, Verena; Ushida, Michele; Lopes, Flavio; Alhadeff, Paula; Ritch, Robert; Prata, Tiago
Abstract Purpose Glaucomatous eyes with disc hemorrhage (DH) have a greater risk of paracentral visual field (VF) loss. However, not every DH eye presents with parafoveal scotoma (PFS), and contributing factors are still to be determined. In the present study, we investigated clinical and ocular factors associated with the presence of PFS in glaucomatous eyes with DH. Methods A case-control study was carried out. One hundred thirty glaucomatous patients with DH were enrolled. They were divided into two groups based on two reliable 24-2 VF tests: those with PFS (defined as ≥3 adjacent points withp  < 5% within the central 10 degrees of fixation, ≥1 point withp  < 1% lying at the innermost paracentral points, in the same hemifield) and those without PFS. Clinical and ocular data from the time of DH detection were compared between groups. Factors associated with the presence of PFS were investigated through logistic regression. Results The PFS group had a higher prevalence of Caucasian patients (82 vs. 47%;p  < 0.01). Eyes with PFS had a more negative spherical equivalent and worse VF mean deviation (MD) index (p  ≤ 0.01). There was a marginally significant intraocular pressure (IOP) difference between eyes with (15 mmHg) and without PFS (18 mmHg) at the time of DH detection (p  = 0.10). Univariable analysis revealed PFS to be significantly associated with Caucasian race (OR, 3.02;p  = 0.004), myopia (<−3 diopters; OR, 3.44;p  = 0.039), and lower IOP (≤16 mmHg; OR, 2.10;p  ≤ 0.047). Multivariable analysis, controlling for VF MD, revealed that only Caucasian race and myopia (as a continuous or categorical variable) remained significant in this model (p  ≤ 0.038). Conclusions Caucasian race and the presence and magnitude of myopia were found to be significantly associated with the presence of PFS in glaucomatous eyes with DH. Our results may help clinicians in the identification and surveillance of these eyes at higher risk of central VF loss.